IMPROVING STUDENTS’ PRONUNCIATION USING WORDUP APPLICATION : A SYISTEMATIC LITERATURE REVIEW - Daffa Nirwana Wahyudi; Nazwa Khalifatunnisa; Farah Fadhilah; Naf’an Tarihoran (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to examine the effectiveness of the WordUp application in improving students’ pronunciation skills within Mobile-Assisted Language Learning (MALL) environments. The rapid growth of digital learning tools has encouraged the integration of mobile applications to provide authentic exposure, individualized practice, and immediate feedback for English as a Foreign Language (EFL) learners. Using a Systematic Literature Review (SLR) method, this research analyzed studies published between 2020 and 2025 from databases such as Google Scholar, ERIC, ScienceDirect, and Mendeley. A total of 690 articles were initially identified, and 6 studies met the inclusion criteria. The findings indicate that WordUp effectively supports vocabulary mastery while offering indirect yet meaningful benefits for pronunciation improvement through audio models, contextual examples, and spaced-repetition features. Although the application is primarily designed for vocabulary learning, students reported increased exposure to accurate pronunciation input and improved clarity in spoken production. However, several limitations were identified, including the lack of comprehensive pronunciation assessment and limited multi-word expression coverage. Overall, WordUp is a valuable supplementary tool that enhances learner motivation, supports autonomous learning, and contributes positively to pronunciation development, especially when integrated with broader speaking-focused instructional strategies.